Endophyte microbial characteristic of soft corals Lobophytum sp and Sinularia sp collected from Maspari Island waters, South Sumatera - Rozirwan M; Muhammad Hendri; Rezi Apri (Research Centre of Inorganic Materials and Complexs, 2018)
Soft corals have bioactive compounds to potential as marine natural products, but the over exploitive to destroy of that ecosystem. Therefor endophyte microbial isolation can be effort to prevent that matters. This research aimed to isolate and characteristic on the entophyte microbial of soft coral Lobophytum sp and Sinularia sp that collated from Maspari island waters. Methodology of research were establishing growth of microbial samples (bacterial and fungal), isolation and characterization. Total of bacteria colony of Lobophytum sp were obtained about 5 isolates, and Sinularia sp were about 4 isolates. The macroscopic characteristic showed that whole bacteria had white colors. That colonies had undulate, entire and curl (the edge of colony) and circular and irregular (for colony shape). For fungal of Lobophytum sp were obtained about 3 isolates, while Sinularia sp had only one isolate. The fungal colonies macroscopic characteristic showed yellow, green and white color, while shaped and edges colonies were thickened. spread, thin, round, dark, and the whole of isolates had filamentous hyphae.